From chemical philosophy to theoretical chemistry : dynamics of matter and dynamics of disciplines, 1800-1950 - Nye, Mary Jo (University of California Press, 1993)
How did chemistry and physics acquire their separate identities, and are they on their way to losing them again? Mary Jo Nye has written a graceful account of the historical demarcation of chemistry from physics and subsequent reconvergences of the two, f.